(untitled) (Human Factors in Design, 2012)
This paper addresses the evaluation of the Cognitive-Walk-Through (CWT) usability method by the application of an experiment with two groups: the control group and the experimental group. While one group carried out an assessment task without the use of a method, the other group used the CWT method. Both groups were intentionally assembled only with designers with the purpose to evaluate the ability of the proposed method: the possibility of the expert to place him or herself as the user. Although both groups came up with similar answers, meaningful differences were noticed. The evaluation of the group that used the method was deeper and more sensitive to the condition of the user. Furthermore, the method proved itself as an important guide in the search for answers focused on the demanded task.